Refractory Stage M Ganglioneuroblastoma With Bone Metastases and a Favorable, Chronic Course of Disease: Description of a Patient Cohort. Issue 1 (21st April 2021) - Tas, Michelle L.; Molenaar, Jan J.; Peek, Annemarie M.L.; Lequin, Maarten H.; Verdijk, Rob M.; de Krijger, Ronald R.; Tytgat, Godelieve A.M.; van Noesel, Max M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Refractory stage M neuroblastoma (NB) is associated with a poor prognosis and a progressive course of disease. Here, we describe a unique group of patients with a discrepant clinical course. Seven histologically confirmed ganglioneuroblastoma (GNB) (n=6) and differentiating NB (n=1) patients were identified who were diagnosed with stage M disease based on iodine-123-metaiodobenzylguanidine avid bone metastases. Six patients started on high-risk treatment, without tumor response (stable disease). Treatment was discontinued before the start of consolidation treatment because of refractory response in all patients. Unexpectedly, after cessation of treatment no progression of disease occurred. In 2 patients, the primary tumors expanded (>25%) very slowly during 1.5 and 3 years, and remained stable thereafter. Metabolically, a slow decrease of urinary homovanillic acid and vanillylmandelic acid levels and iodine-123-metaiodobenzylguanidine avidity was observed. All patients are alive with presence of metastatic disease after a median follow-up of 17 years (range: 6.7 to 27 y). Interestingly, at diagnosis, 6 patients were asymptomatic, 6 patients had GNB morphology, and 5 patients had meningeal metastases. These are all features seen in only a small minority of stage M patients. This GNB entity illustrates the clinical heterogeneity of neuroblastic tumors and can be used to further study the developmental origin of different NB subtypes.